2014
DOI: 10.5507/bp.2013.070
|View full text |Cite
|
Sign up to set email alerts
|

Addition of platelet concentrate to Dermo-Epidermal Skin Graft in deep burn trauma reduces scarring and need for revision surgeries

Abstract: Backround Deep skin burn injuries, especially those on the face, hands, feet, genitalia and perineum represent significant therapeutic challenges. Autologous dermo-epidermal skin grafts (DESG) have become standard of care for treating deep burns. Additionally, human autologous thrombin activated autologous platelet concentrate (APC) has gained acceptance in the setting of wounds. While each of these interventions has been independently shown to accelerate healing, the combination of the two has never been eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…There are a number of studies showing that the use of autologous PRP can improve the results of wound‐healing processes, as well as in cases of poorly healing wounds. Several controlled studies have given statistically significant evidence that the use of PRP leads to the acceleration of wound healing . There are three controlled studies on humans that reported of improvement of wound healing with regard to healing time, the quality of life, and reduction of pain .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of studies showing that the use of autologous PRP can improve the results of wound‐healing processes, as well as in cases of poorly healing wounds. Several controlled studies have given statistically significant evidence that the use of PRP leads to the acceleration of wound healing . There are three controlled studies on humans that reported of improvement of wound healing with regard to healing time, the quality of life, and reduction of pain .…”
Section: Discussionmentioning
confidence: 99%
“…Several controlled studies have given statistically significant evidence that the use of PRP leads to the acceleration of wound healing. [16][17][18][19][20][21][22][23][24][25][26] There are three controlled studies on humans that reported of improvement of wound healing with regard to healing time, the quality of life, and reduction of pain. 17,18,25 According to a prospective controlled study of Hom et al, epithelialisation and granulation formation appeared 3 days earlier in the experimental group where PRP was used, 16 while it was established in our study that granulation formation also started 3 days earlier and epithelialisation 4 to 6 days earlier in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a cohort study in 18 burn patients treated with a split thickness skin graft (SSG) and autologous platelet concentrate, resulted in less pain and earlier discharge compared with institutional controls who did not receive SSG with autologous platelet concentrate. However, this control group was described insufficiently …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recently some reports were published with positive results of PRP in combination with adipose cells for scar treatment; therefore, there might be an indication for PRP in the reconstructive aspect of burn treatment. On the other hand, in another study, long-term follow-up results did not show significant differences in scar quality in patients treated with PRP combination [86].…”
Section: Prp In Burnsmentioning
confidence: 77%